Effects of Climate Change Stressors on the Prokaryotic Communities of the Antarctic Sponge Isodictya kerguelenensis - Rondon, Rodolfo; González-Aravena, Marcelo; Font, Alejandro; Osorio, Magdalena; Cárdenas, César A. (Frontiers in Ecology and Evolution, 2020)
Microbial symbionts of marine sponges play important roles for the hosts and also for the ecosystems. The unique tolerance of marine sponge to a wide diversity of microbial symbionts allows them to acquire a wide variety of “evolutionary solutions” to environmental challenges. Ice scour is one of the main forces structuring Antarctic benthic communities and its effect is expected to increase as further warming is projected for the Western Antarctic Peninsula (WAP). The interaction of these physical drivers may have a significant impact shaping the microbiome of Antarctic sponges under current and future scenarios of climate change. The aim of this research was to assess how stressors such as warming and injuries produced by ice scour, affect the microbiome of the marine Antarctic sponge Isodictya kerguelenensis. under current and predicted scenarios. Individuals of I. kerguelenensis were sampled in shallow waters (10 m) off the coast of Doumer Island, Palmer Archipelago, WAP. In order to mimic the effect of tissue damage produced by ice scour, tissue samples were taken at day 0 (T0d) and 15 (T15d) from individuals placed in control (0.5 °C) and two temperature treatments (3 and 6°C). Our analysis of 16S libraries from the V4-V5 region revealed two phyla of Archaea and 22 of Bacteria. Proteobacteria and Bacteroidetes were the most representative in terms of both number of OTUs and sequence abundances. The analysis at OTU level showed significant effect of injury and treatment. Principal Coordinates Analysis (PCoA) showed a clear group of uninjured sponges and three other groups of injured sponges according to temperature. Our results also showed a group of OTUs that were only present in injured sponges, being potential markers of sponge damage. Our study suggests that disturbance produced by icebergs may have direct impact on the sponge microbiome. Future climate change scenarios with warming and increases in iceberg impacts may lead to prokaryotic symbiont disruption on sponge species, having potential cascading effects for the host and the functional roles they play in the Antarctic ecosystem; however, the potential effects of this disruption are yet to be further studied.